Influence of Genetic Polymorphism Towards Pulmonary Tuberculosis Susceptibility - Harishankar, Murugesan; Selvaraj, Paramasivam; Bethunaickan, Ramalingam (Frontiers in Medicine, 2018)
Tuberculosis (TB) still remains the major threat for human health worldwide. Several case-control, candidate-gene, family studies and genome-wide association studies (GWAS) suggested the association of host genetic factors to TB susceptibility or resistance in various ethnic populations. Moreover, these factors modulate the host immune responses to tuberculosis. Studies have reported genetic markers to predict TB development in human leucocyte antigen (HLA) and non-HLA genes like killer immunoglobulin-like receptor (KIR), toll-like receptors (TLRs), cytokine/chemokines and their receptors, vitamin D receptor (VDR) and SLC11A1 etc. Highly polymorphic HLA loci may influence antigen presentation specificities by modifying peptide binding motifs. The recent meta-analysis studies revealed the association of several HLA alleles in particular class II HLA-DRB1 with TB susceptibility and valuable marker for disease development especially in Asian population. Case-control studies have found the association of HLA-DR2 in some populations but not in other populations, this could be due to ethnic specific association of gene variants. Recently, GWAS conducted in case-control and family based studies in Russia, Chinese Han, Morocco, Uganda and Tanzania revealed the association of genes such as ASAP1, Alkylglycerol monooxygenase (AGMO), Forkhead BoxP1 (FOXP1), C-terminal domain phosphatase 1 (UBLCP1) and intergenic SNP rs932347C/T with TB. Whereas, SNP rs10956514A/G were not associated with TB in western Chinese Han and Tibetan population. In this review, we summarize the recent findings of genetic variants with susceptibility/resistance to TB.